2020
DOI: 10.1007/s11606-020-05634-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Mortality Associated with Non-selective Antimuscarinic medications in Older Adults with Dementia: a Retrospective Study

Abstract: BACKGROUND: Selective antimuscarinics may offer a favorable safety profile over non-selective antimuscarinics for the management of overactive bladder (OAB) in patients with dementia. OBJECTIVE: To test the hypothesis that non-selective antimuscarinics are associated with increased risk of mortality compared to selective antimuscarinics in older adults with dementia and OAB. DESIGN: Propensity score-matched retrospective newuser cohort design among Medicare beneficiaries in community settings. PATIENTS: Older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…These actions probably result in its perturbations on the functional activities of electrically excitable cells (e.g., GH 3 or mHippoE-14 cells), in the case that in vivo findings occur. Whether the impairment of cognitive function after long-term administration of SOL [20][21][22][23][24][25][26][27][28][29][30][31] could be intimately connected with its stimulation of I K(M) in central neurons remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These actions probably result in its perturbations on the functional activities of electrically excitable cells (e.g., GH 3 or mHippoE-14 cells), in the case that in vivo findings occur. Whether the impairment of cognitive function after long-term administration of SOL [20][21][22][23][24][25][26][27][28][29][30][31] could be intimately connected with its stimulation of I K(M) in central neurons remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has recently accumulated that the treatment with SOL could be linked to an increased risk of the impairment in cognitive functions [20][21][22][23][24][25][26][27][28][29][30][31]. Earlier reports have also reported the ability of this drug to influence the muscarinic activity in cerebral cortex and hippocampus [67,68].…”
Section: Stimulatory Effect Of Sol On Ik(m) Present In Mhippoe-14 Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have also associated antimuscarinics use with increased occurrence of falls/fractures 45,46 and hospitalizations, 46,47 , and only one study focused on the differential risk based on the selectivity of antimuscarinics. Our previous study evaluated the comparative risk of all‐cause mortality from nonselective versus selective antimuscarinic use in the same population as in the current study and identified 50% increased risk of up to 180‐day mortality (HR 1.50; 95% CI 1.04–2.16) 48 . Others have specifically focused on the association between individual antimuscarinics and outcomes like falls/fractures or hospitalizations 49,50 .…”
Section: Discussionmentioning
confidence: 87%
“…[24][25][26] Some studies have also associated antimuscarinics use with increased occurrence of falls/fractures 45,46 and hospitalizations, 46,47, and only one study focused on the differential risk based on the selectivity of antimuscarinics. Our previous study evaluated the comparative risk of all-cause mortality from nonselective versus selective antimuscarinic use in the same population as in the current 48 Others have specifically focused on the association between individual antimuscarinics and outcomes like falls/fractures or hospitalizations. 49,50 Gomes et al, compared oxybutynin versus tolterodine, and reported no difference in the risk of falls, no difference in the risk of fractures, but 12% significant increase in the risk of all-cause hospitalizations (adjusted HR 1.12, 95% CI 1.07-1.17).…”
Section: F I G U R E 2 Patient Attrition Flowchart [Colour Figure Canmentioning
confidence: 99%